Mixed use and residential tenants' rights : The Landlord and Tenant Act 1987 and Leasehold Enfranchisement /: The Landlord and Tenant Act 1987 and Leasehold Enfranchisement. (2016) - Dollar, Peta; Thompson-Copsey, Sarah
No abstract available